Somatostatin-derived amyloidosis: a novel type of amyloidosis associated with well-differentiated somatostatin-producing neuroendocrine tumours. (2nd January 2022) - Van Treeck, Benjamin J.; Dasari, Surendra; Kurtin, Paul J.; Theis, Jason D.; Nasr, Samih H.; Zhang, Lizhi; Yasir, Saba; Graham, Rondell P.; McPhail, Ellen D.; Said, Samar
Abstract: Objective: To report the clinicopathologic and proteomic characteristics of a novel form of amyloidosis derived from the precursor protein somatostatin. Materials and methods: Cases were identified by searching the Mayo Clinic amyloid liquid chromatography and tandem mass spectrometry (LC-MS/MS) typing database from 1 January 2008 to 1 September 2020 for specimens with the amyloid signature proteins and abundant somatostatin, in the absence of other amyloid precursor proteins. All available medical records and pathologic materials were examined. Results: Somatostatin-derived amyloid deposits were found in four patients, two females and two males, with a median age of 61.5 years (range 47–73 years). One patient also had neurofibromatosis-1. The amyloid in each case was associated with a well-differentiated, somatostatin-producing neuroendocrine tumour arising in the small bowel or pancreas. The amyloid deposits were Congo Red-positive and were readily identified by LC- MS/MS analysis. Somatostatin was present exclusively in somatostatin-associated amyloid cases ( p < .001), compared to small bowel and pancreas amyloidosis cases of other types. Long-term follow-up is available for one patient who is alive 6 years after initial presentation. Conclusion: We propose that somatostatin-related amyloidosis is a novel localised human amyloid type that arises in association with well-differentiated somatostatin-producing enteropancreatic neuroendocrine tumours. Treatment of the associated neuroendocrine tumour may be adequate therapy for these patients.